The atomic fortress that time forgot [plutonium production plant]. - Guizzo, E.
The future of the world's first full-scale nuclear reactor, called the B Reactor, remains uncertain in the face of the US Dept. of Energy's effort to clean up the radioactive and chemical contamination at Hanford. Established by the Manhattan Project during World War II, the B Reactor is part of the Hanford site, a 1500-square kilometer plutonium production complex in the state of Washington. A study has been commissioned to assess the possibility of converting some of the Manhattan Project's historic sites into parks and museums in order for future generations to learn about the Project and its impact on world history.
Keywords: Atomic fortress; Industrial-scale operation; Neutron emission; Nuclear reactions; Plutonium making reactor; Slugs natural uranium